The mass distribution of Galactic double neutron stars: constraints on the gravitational-wave sources like GW170817. Issue 4 (5th August 2019) - Zhang, Jianwei; Yang, Yiyan; Zhang, Chengmin; Yang, Wuming; Li, Di; Bi, Shaolan; Zhang, Xianfei
ABSTRACT: The merger event of double neutron star (DNS) system (GW170817) was detected by the gravitational-wave (GW) detectors (Advanced LIGO and Advanced Virgo) in 2017 for the first time, so their mass distribution has become a significant topic with the new round GW hunting (O3) in 2019. A few models (e.g. Gaussian, two-Gaussian, or mixture-Gaussian) were adopted to draw the mass distribution of observed Galactic DNS systems, however, there is no a confirmed model now due to the small size of DNS samples ( N < 20). Here we focus on determining the most probable distribution ranges of DNS masses without model selection by assuming the neutron star masses to be uniformly distributed between the lower and upper bounds. We apply a Bayesian analysis and Markov chain Monte Carlo simulation to 15 Galactic DNS systems, and obtain that the component masses of DNS systems should mainly fall in the range of 1.165–1.590 M⊙, and the predominant ranges for the total mass, mass ratio, and chirp mass lie in 2.535–2.867 M⊙, 0.741–0.995, and 1.115–1.237 M⊙, respectively. Our results are in agreement with the properties of DNS in GW170817, whose 90 per cent credible intervals for the component masses, total masses, mass ratio, and chirp masses are 1.16–1.60 M⊙, 2.73_-0.01^+0.04 M_, 0.73–1.00, and1.186_-0.001^+0.001 M_, respectively. The above similarity is an important indicator that reveals the source of GW170817 to be a DNS system from the galaxy NGC 4993, and our results can be tested by the forthcoming GW hunting O3.